2014
DOI: 10.1039/c4ra07075e
|View full text |Cite
|
Sign up to set email alerts
|

Induction of self-structure in polyriboadenylic acid by the benzophenanthridine plant alkaloid chelerythrine: a spectroscopic approach

Abstract: Induction of self-structure in polyriboadenylic acid by chelerythrine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 65 publications
(87 reference statements)
1
19
0
Order By: Relevance
“…Such fluorescence energy transfer has been reported in the case of CHL-DNA binding 25 and CHL-poly(A) binding. 28 Thus from the present study it can be concluded that both DNA as well as RNA base doublet and triplet can transfer energy to CHL when the alkaloid is intercalated in the DNA/RNA structure.…”
Section: Energy Transfer and Quantum Yieldsupporting
confidence: 54%
See 2 more Smart Citations
“…Such fluorescence energy transfer has been reported in the case of CHL-DNA binding 25 and CHL-poly(A) binding. 28 Thus from the present study it can be concluded that both DNA as well as RNA base doublet and triplet can transfer energy to CHL when the alkaloid is intercalated in the DNA/RNA structure.…”
Section: Energy Transfer and Quantum Yieldsupporting
confidence: 54%
“…The concentration of CHL was checked spectrophotometrically by using a known extinction value of 37 060 M À1 cm À1 at 316 nm. 28 To avoid light induced photochemical change CHL solutions were kept in the dark all time. A molar extinction value of poly(U) and A.U was 9350 and 7140 M À1 cm À1 at 260 nm respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports on poly(rA) binding activity of the plant alkaloid chelerythrine (Figure 3) indicated that this natural compound was also able to induce poly(rA) self-structures with the formation of a poly(rA) helix that showed a cooperative melting transition in circular dichroism experiments [31].…”
Section: Poly(ra) As a Target In Anticancer Approachesmentioning
confidence: 95%
“…Recent reports on poly(rA) binding activity of the plant alkaloid chelerythrine ( Fig. 3 ) indicated that this natural compound was also able to induce poly(rA) self-structures with the formation of a poly(rA) helix that showed a cooperative melting transition in circular dichroism experiments [ 31 ].…”
Section: Reviewmentioning
confidence: 99%